Celluloid Democracy Cinema and Politics in Cold War South Korea - Kim, Hieyoon (University of California Press, 2023)
The first book to offer a history of film activism in post-1945 South Korea, Celluloid Democracy tells the story of the Korean filmmakers, distributors, and exhibitors who reshaped cinema in radically empowering ways through decades of authoritarian rule. Employing tactics that ranged from representing the dispossessed on the screen to redistributing state-controlled resources through bootlegging, these film workers explored ideas and practices that simultaneously challenged repressive rule and pushed the limits of the cinematic medium. Drawing on archival research, film analysis, and interviews, Hieyoon Kim shows how Korean film workers during the Cold War reclaimed cinema as an ecology in which democratic discourses and practices could flourish. "Celluloid Democracy is brilliant; the scholarship is admirable. Hieyoon Kim has written an extraordinarily captivating account of the film workers, educators, intellectuals, and radical film activists in Cold War South Korea who dreamed of a better world and struggled to achieve democracy through cinema until the end of military rule in 1987. This remarkably readable and well-researched study deserves a wide audience." - SANGJOON LEE, author of Cinema and the Cultural Cold War: US Diplomacy and the Origins of the Asian Cinema Network "A fascinating and polished piece of scholarship. I don't know of any other book quite like this one. Moving away from the traditional focus on auteurs and film texts, Kim masterfully draws our attention to the critical yet often forgotten figures working on the margins of the postwar film scene, filling in some substantial gaps in our understanding of this period." - CHRISTINA KLEIN, author of Cold War Cosmopolitanism: Period Style in 1950s Korean Cinema